TEENAGE PREGNANCY AND SCHOOL ATTRITION: AN ASSESSMENT OF ACADEMIC PERFORMANCE AMONG GIRL-CHILD EDUCATION IN SECONDARY SCHOOLS IN TARABA STATE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
Teenage pregnancy remains a significant barrier to the educational advancement of the girl-child in Sub-Saharan Africa. In Taraba State, Nigeria, prevailing socio-cultural and economic conditions create a context in which adolescent pregnancy frequently coincides with critical stages of secondary education, thereby posing serious threats to academic progression and completion. This study employed a descriptive survey research design, sampling 600 female students from selected public and private secondary schools across urban and rural areas of Taraba State. Data were collected using a structured questionnaire and analyzed using mean scores and standard deviations, with a decision benchmark of 2.50. The findings revealed a high prevalence of teenage pregnancy, with 36.3% of respondents reporting prior pregnancy experience. Most cases occurred among students aged 17–19, contributing to over-aged schooling and academic stagnation. Key determinants identified include lack of parental guidance, exposure to media and early marriage. Hypothesis testing showed that teenage pregnancy significantly affects academic performance and is strongly associated with school dropout. Additionally, affected students experience stigma, low self-esteem, and emotional distress, although family support serves as a mitigating factor. The study concludes that teenage pregnancy in Taraba State is a multifaceted problem that undermines educational attainment and perpetuates socio-economic inequality. It recommends a multi-sectoral approach involving comprehensive sexuality education, school-based counseling services, parental engagement, and government-led economic support initiatives.